Reassessment of the binary, ternary, and quaternary interactions in mixed electrolytes from thermodynamic quantities: the systems with uncommon ions containing hydrophobic character - Kumar, Anil (Journal of Physical Chemistry B, 2005)
Accurate estimates of the binary, ternary, and quaternary interactions in aqueous ionic mixtures with uncommon ions with hydrophobic character are presented. For this purpose, the values of the excess Gibbs free energy of mixing, Delta(m)G(E), obtained from our earlier isopiestic osmotic coefficients (Kumar, A. J. Phys. Chem. B 2003. 107, 2808) for the mixtures of NaCl with four guanidinium (Gn(+)) salts-CH(3)COOGn, GnNO(3), GnClO(4), and Gn(2)SO(4) are analyzed with the help of the method developed by Leifer and Wigent. The methodology of Leifer and Wigent is based on the equations of Scatchard-Rush-Johnson and Friedman's cluster integral expansion theory. The Scatchard-Rush-Johnson theory explicitly considers the quaternary and higher-order ionic interactions in the mixtures as compared to the specific ion interaction theory of Pitzer, which accounts for binary and ternary interactions only. The contributions due to binary, ternary, and quaternary interaction terms to total Delta(m)G(E) are estimated and discussed critically. Also, the interaction between the same two cations, for example, Gn(+)-Gn(+), is estimated and found significant, which otherwise cannot be obtained by the use of Pitzer's theory. The information obtained from the analysis of Delta(m)G(E) is also supported by the newly measured excess volumes of mixing, Delta(m)V(E), at 298.15 K. The individual contributions of the binary, ternary, and quaternary interaction terms to total Delta(m)V(E) are described. The binary, ternary, and quaternary interaction terms for both Delta(m)G(E) and Delta(m)V(E) are analyzed in terms of Friedman's cluster integral expansion theory.

Recent applications of chloroaluminate ionic liquids in promoting organic reactions - Kumar, Anil; Sarma, Diganta (Symposium on Ionic Liquids - Fundamentals, Progress, Challenges and Opportunities held at the 226th American-Chemical-Society National Meeting, 2005)
Chloroaluminate ionic liquids composed of AICl(3) and organic cations can promote a variety of organic reactions. The composition of these chloroaluminate ionic liquids governs the acidity and basicity of solvent media, in which the reactions are carried out. Useful physico-chemical properties of these ionic liquids and the recent work on their role in accelerating organic reactions are described in the present article.

Rare earth metal triflates promoted diels-alder reactions in ionic liquids - Sarma, Diganta; Kumar, Anil (Applied Catalysis A-General, 2008)
Rare earth metal triflates, when used with ionic liquids can promote Diels-Alder reactions carried out with different dienes and dienophiles suggesting an enhancement in the catalytic power of the triflates in ionic liquids. It is possible to recover and reuse the ionic liquid phase with triflates to give comparable yields and stereoselectivities even after six cycles. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: Diels-Alder reactions; ionic liquids; rare earth metal triflates

Reversal from endothermic to exothermic behavior of imidazolium-based ionic liquids in molecular solvents - Rai, Gitanjali; Kumar, Anil (Chemical Physics Letters, 2010)
In this communication, we present an interesting reversal in the enthalpic behavior from endothermic to exothermic on increasing the carbon chain length attached to the imidazolium ring in the imidazolium-based ionic liquids. A systematic investigation is presented on the excess partial molar enthalpy, H(IL)(E) directly measured using isothermal titration calorimeter at 298.15 K for the interactions operating between cation and anion of four imidazolium ionic liquids with aqueous and various non-aqueous solvents. This reversal behavior is analyzed in terms of hydrophobic and solvation effects. (C) 2010 Published by Elsevier B.V.